EFFECT OF PQRST METHOD ON FIFTH-GRADE STUDENTS’ SPEAKING SKILLS AT MIN 12 BANDAR LAMPUNG - Adinda Thalia; Uswatun Khasanah; Yuli Yanti (Al-Hijr: Journal of Adulearn World, 2026)
This study aims to analyze the effect of the Preview, Question, Read, Summarize, and Test (PQRST) method on students’ speaking skills. The participants of this study were fifth-grade students who experienced difficulties in expressing ideas, organizing speech, and demonstrating confidence during speaking activities. A quantitative approach with a quasi-experimental design using a posttest-only control group was employed. The sample was selected through purposive sampling techniques. Data were collected through speaking tests and documentation. The findings revealed that students taught using the PQRST method obtained a higher average score (59.0) than students taught using the SQ3R method (31.8). Statistical analysis further indicated that the PQRST method had a significant effect at the 5% significance level. The novelty of this study lies in the implementation of the PQRST method as a structured learning strategy that improves not only reading comprehension but also speaking skills. The results suggest that the PQRST method can serve as an innovative alternative in language learning. This study contributes to the development of effective active learning strategies that encourage students’ participation, confidence, and communication skills in educational settings.